EFEKTIVITAS MODEL TEAMS GAMES TOURNAMENT (TGT) DALAM MENINGKATKAN PEMAHAMAN NILAI-NILAI PANCASILA SISWA SEKOLAH DASAR: KAJIAN LITERATUR - Wulandari Rahayu, Shindi; Mulyadiprana, Ahmad; Moh Irma Ari Irawan, Tb (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the Teams Games Tournament (TGT) learning model in improving elementary school students’ conceptual understanding of Pancasila values through a literature review. This study is motivated by the low level of students’ conceptual understanding of Pancasila values, where students tend to memorize rather than understand and apply these values in their daily lives. This research employs a qualitative approach using a literature review method by analyzing various relevant studies that have been published. The data were obtained from scientific articles selected based on specific criteria related to the TGT model, elementary school learning, and conceptual understanding of Pancasila values. The data analysis technique used content analysis, which includes data reduction, data display, and conclusion drawing. The results of the study indicate that the TGT learning model is effective in improving students’ conceptual understanding, learning motivation, activeness, and learning outcomes. Learning activities through group discussions, academic games, and healthy competition create an active and enjoyable learning environment, which helps students understand and apply Pancasila values in their daily lives. Therefore, the TGT model can be recommended as an alternative learning model in Pancasila education at the elementary school level.